Study of Science Practicum in Junior High School, Sukoharjo, Indonesia - Sarah, Farikha Muya; Agustina, Putri; Hastowati, Harini (Proceeding of International Conference on Biology Education, Natural Science, and Technology, 2023)
Practicum or experiments in the laboratory are needed to support science learning activities. According to Permendiknas Number 24 of 2007 the educational process requires supporting facilities and equipment so that the learning process can run optimally. In the implementation of science practicum, there are benefits, including arousing motivation to learn science and giving students the opportunity to satisfy their curiosity, as a source of learning a scientific approach. The purpose of this study was to determine the quality of facilities and infrastructure, as well as the implementation of science practicum in research junior high schools. The type of research used is descriptive qualitative with data collection techniques using observation, documentation, interviews, and questionnaires. The results showed that the quality of science laboratory facilities and infrastructure in junior high schools was included in the good category as stated in Permendiknas Number 24 of 2007 is evidenced by an average percentage of 77.42%. The implementation of science practicum is in a very good category where the average percentage obtained is 89.25%. The results of the questionnaire showed that the average percentage of science practicum implementation was 65.8% in the good category, in the sense that the implementation of science practicum class IX in the even semester went well.